Supervisi Akademik sebagai Formalitas Administratif dan Dampaknya terhadap Profesionalisme Guru Sekolah Dasar - Putri Hidayati; Nurul Hikmah; Ahmad Farhan Alisnaini; Ismarina Rosida; Yetty Morelent; Erwinsyah Satria (STKIP Subang, 2026)
This study aims to analyze the implementation of academic supervision that tends to be merely procedural and its impact on teachers’ professionalism in sustaining the quality of learning in elementary schools. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, classroom observations, and document analysis, and were analyzed using an interactive analysis model involving data reduction, data display, and conclusion drawing. The findings reveal that academic supervision has been conducted in a scheduled and administrative manner but has not fully functioned as a continuous professional development process. Teachers tend to demonstrate more structured and varied teaching practices during supervision sessions but revert to minimal instructional practices in daily teaching. This indicates that learning quality is still influenced by external control rather than driven by teachers’ internal professional awareness. The lack of reflective dialogue and follow-up actions also hinders the development of a sustainable culture of instructional improvement. The study highlights the importance of collaborative, reflective, and continuous academic supervision in fostering teacher professionalism and maintaining consistent learning quality